PEMETAAN SEBARAN PENYAKIT FARINGITIS AKUT BERBASIS SISTEM INFORMASI GEOGRAFIS DI PUSKESMAS CANDILAMA TAHUN 2023 - Shafira Berlian Tabroni; Setya Wijayanta; Asharul Fahyudi (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2022)
Acute pharyngitis is one of the diseases caused by viral bacterial infections. In the report of the top 10 diseases in the Candilama Health Center, acute pharyngitis disease was ranked first. In order to facilitate health surveillance, mapping based on Geographic Information Systems is carried out. However, at the Candilama Health Center, mapping the distribution of acute pharyngitis has never been carried out in the Candilam Health Center work area. This study used the method of document study and observation on the object of research and mapping the spread of acute pharyngitis in the working area of the Candilama Health Center, The data used in this study were data on visits of acute pharyngitis patients based on age group, gender, and based on work area. The results of this study show that based on mapping that has been carried out, the area with the most cases of acute pharyngitis is Jomblang sub-district, one of these factors in terms of population density, for the age group most suffered by toddlers in the toddler age group, they are usually susceptible to disease in the respiratory tract and for the sex group, many are suffered by women because women have a different respiratory structure from man.